Analysis of T cell subsets and beta chemokines in patients with pulmonary sarcoidosis. Issue 5 (May 1997) - Iida, K; Kadota, J; Kawakami, K; Matsubara, Y; Shirai, R; Kohno, S
Abstract : BACKGROUND: Sarcoidosis is a systemic granulomatous disorder of unknown origin characterised by accumulation of T lymphocytes and macrophages in multiple organs. Several cytokines and adhesion molecules may contribute to the accumulation of T lymphocytes in pulmonary sarcoidosis. The distribution of T lymphocyte subsets, T cell bearing CD11a and beta chemokines such as regulated on activation normal T expressed and secreted (RANTES), macrophage inflammatory peptide 1 alpha (MIP-1 alpha), and macrophage chemoattractant protein 1 (MCP-1) in bronchoalveolar lavage (BAL) fluid and peripheral blood were compared in untreated patients with sarcoidosis and normal subjects. METHODS: Flow cytometric analysis with monoclonal antibodies to cell surface antigens was used to identify T lymphocyte subsets in the BAL fluid of untreated patients with sarcoidosis (n = 40)--either without (group A, n = 12) or with (group B, n = 28) radiological evidence of pulmonary involvement--and in 22 normal subjects. The level of different beta chemokines was estimated by enzyme linked immunosorbent assay (ELISA). RESULTS: A high percentage of CD3+ cells, CD4+ cells expressing HLA-DR antigen, and a high CD4/CD8 ratio were detected in the BAL fluid of patients compared with normal subjects. In particular, CD4+ CD29+ memory T cells were significantly increased in patients with sarcoidosis. Furthermore, these cells were higher in those in group B than group A. The level of RANTES in the BAL fluid of patients was significantly higher than in normal subjects and correlated well with the percentage, number, and expression of CD29 on CD4 cells. The expression of CD11a (alpha chain of lymphocyte function associated antigen-1, LFA-1) on CD3+ cells in the BAL fluid of patients with sarcoidosis was not different from that of normal subjects. However, the expression of CD11a on CD3+ cells in the BAL fluid of patients in group A was significantly lower than that of patients in group B and normal subjects. CONCLUSIONS: These results suggest a possible interaction between activated memory T cells bearing CD11a and RANTES which may contribute to the pulmonary involvement in patients with sarcoidosis.